Credit Constraints in General Equilibrium: Experimental Results - Antoni Bosch-Domènech; Joaquim Silvestre (University of California, Department of Economics, 1995)
Our work attempts to investigate the influence of credit tightness or expansion on activity and prices in a multimarket set-up. We report on some doubleauction, two-market experiments where subjects had to satisfy an inequality involving the use of credit. The experiments display two regimes. characterized by high and low credit availability. The critical vakre of credit at the common boundary of the two regimes has a compelling interpretation as the maximal credit use at the Arrow-Debreu equilibrium of the abstract economy naturally associated to our experimental environment. Our main results are that changes in the availability of credit: (a): have minor and unsystematic effects on real and nominal variables in the high-credit regime; (b): have substantial effects, both real and nominal, in the low-credit regime.
Keywords: 330